Structural health monitoring of transmission line towers through evaluation of natural frequency - Balagopal, R.; Rao, N. Prasad; Rokade, R.P.; Palani, G.S. (Journal of Structural Engineering, 2024)
For structural health monitoring of Transmission Line (TL) towers, accurate evaluation of natural frequency is one of the requirements. The damage detection studies of TL towers through change in natural frequency is gaining importance, because the stiffness loss due to damage inflicted in load bearing member of TL tower leads to reduction in its natural frequency. Further, the estimation of natural frequency of TL tower is important to evaluate its response under gusty wind and for determination of impact force under broken conductor loads. The leg, bracing and tie member of TL lattice towers are joined through bolted connections, which are modelled with conventional pin joint assumption considering only axial stiffness of joining members. However, the natural frequency predicted by using this pin joint model do not match with experimental results due to ignorance of rotational stiffness induced by eccentric load transfer. Hence, the authors proposed a modified bolted connection model considering both axial and rotational stiffness. In this paper, a semi-empirical approach is proposed for evaluation of natural frequency by using a modified bolted connection model and the same is validated with the experimental investigations on TL tower sub-panel through the push-pull mechanism. The experimentally determined natural frequency of TL tower panel is in close agreement with the natural frequency evaluated by using the modified bolted connection model. It is observed that the maximum difference in the natural frequency obtained from the experiments and the modified bolted connection model is 18% compared to 30% difference with conventional pin joint assumed in FE modelling of TL towers. Further, the proposed method is validated on full scale prototype tested 240 kV TL tower for determination of natural frequency and the maximum difference is found to be within 12% with modified bolted connection model compared to 23% with pin joint model. Thus, modeling of flexible behaviour of bolted connection with rotational and axial stiffness plays a significant role in determining the dynamic characteristics such as natural frequency for structural health monitoring of TL towers.